Program to Promote Behaviors Prevention of Coronavirus – 2019 (COVID -19) Disease of Parents Pre School-Aged Children in Child Development Center - Faengphong, Natanong; Panyatanakun, Nattida; ฺBoonmun Wisanee (Journal of The Royal Thai Army Nurses, 2023)
This study aimed to determine the preventive behaviors program coronavirus disease 2019. The participants were 60 of parents of pre-school-aged children whose divided into experimental group (n = 30) and comparison group (n = 30). These participants were randomly selected by using the multistage sampling technique. The research instruments were the preventive behaviors program, perceived susceptibility questionnaire, perceived severity questionnaire, perceived benefits questionnaire, perceived barriers questionnaire, and preventive behaviors questionnaire. Data were analyzed using percentage, mean, standard deviation, Chi-Square, Fisher’s exact test, and independent t-tests. The results revealed that after the experimental group participated the preventive behaviors program they had a high level of mean score of perceived susceptibility and perceived severity (M = 4.10, SD = 0.43; M = 4.19, SD = 0.58) respectively. They had the highest level of mean score of perceived benefits of preventive behaviors (M = 4.75, SD = 0.35). They had low mean score of perceived barriers to preventive behaviors regarding COVOD-19 (M = 1.65, SD = 0.52). They also had preventive behaviors as regularly (M = 2.73, SD = 0.44). The experimental group had perceived susceptibility, perceived severity, and perceived benefits of COVOD-19 preventive behaviors statistically significant higher than the comparison group (t = 1.320, p = .020, t = 2.132, p = .019, t = 1.905, p = .031 and t = 2.180, p = .019 respectively) respectively. In addition, the experimental group had perceived barriers statistically significant higher than the comparison group (t = -2.083, p = .041).